The Existence Of Israiliyyat In The Interpretation Of Bil Ma'tsur (Study Of Muhammad Husein Al-Zahabi's Thoughts In The Book Israiliyyat) - Muamar Fatoni; Abdul Matin Bin Salman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The orientation of thinking towards bi-Alma'tsur interpretation is not without weaknesses as stated by Aldzahabi.. The narration of Al-Qur’an interpretation using Israiliyyat has occurred since the time of the Companions and then developed rapidly during the tabi'in era, this happened because on the other hand Al- The Koran is similar to the Torah and Gospel, especially about the stories of previous prophets and people, but the Koran only mentions it globally and is not detailed. This research method uses a library method by describing data related to Israiliyyat in the tafsir bil ma'tsur period by codifying books by Muhammad Husein al-Zahabi related to Israiliyyat. After conducting studies and analysis, this research concludes that al-Zahabi is of the opinion that any Israiliyyat narration that is appropriate and in line with the Islamic religion is permissible to narrate it. As for what is not in accordance with Islamic law or does not make sense, it is not permissible to narrate it. Whereas the history of Israiliyyat is kept silent by the Shari'a or there are no arguments that strengthen or weaken it, the law is tawaqquf which means neither justifying nor blaming it.